A Tale of Two Oceans: Market Integration Over the High Seas, 1800-1940 - Giovanni Federico (European Historical Economics Society (EHES), 2011)
Long-range market integration is an essential component of globalization but it is still comparatively under-researched. The conventional wisdom relies heavily on the case of Atlantic trade in the period after 1870. This paper covers also the Indian Ocean and extends the period under consideration, from Waterloo to World War Two. Integration started in first half of the 19th century, and timing and extent of convergence differed substantially among products. The second part of the paper analyses the causes of the process with a panel regression and puts forwards a tentative estimate of its welfare effects. The key message of the paper is that simple generalizations about the first globalization are not good substitutes for empirical research.
Keywords: 330